2007
DOI: 10.4049/jimmunol.178.4.2483
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for Advanced Glycation Endproducts Mediates Neutrophil Migration across Intestinal Epithelium

Abstract: Receptor for advanced glycation endproducts (RAGE) is an Ig superfamily cell surface receptor that interacts with a diverse array of ligands associated with inflammatory responses. In this study, we provide evidence demonstrating that RAGE is involved in inflammatory responses in the intestines. We showed that RAGE is expressed in intestinal epithelial cells, primarily concentrated at the lateral membranes close to the apical cell junction complexes. Although RAGE expression was low in epithelium under normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 66 publications
3
54
1
Order By: Relevance
“…14 In contrast, Zen et al demonstrated in an in vitro assay that fMLP-induced transmigration of human neutrophils through the human intestinal epithelial cell line T84 was dependent on the presence of epithelial RAGE that bound neutrophil-expressed Mac-1. 15 These findings implicate an important role of both endothelial and neutrophil expressed RAGE in Mac-1-dependent neutrophil recruitment during inflammation.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…14 In contrast, Zen et al demonstrated in an in vitro assay that fMLP-induced transmigration of human neutrophils through the human intestinal epithelial cell line T84 was dependent on the presence of epithelial RAGE that bound neutrophil-expressed Mac-1. 15 These findings implicate an important role of both endothelial and neutrophil expressed RAGE in Mac-1-dependent neutrophil recruitment during inflammation.…”
Section: Introductionmentioning
confidence: 88%
“…14 In contrast, Zen et al demonstrated in an in vitro assay that fMLP-induced transmigration of human neutrophils through the human intestinal epithelial cell line T84 was dependent on the presence of epithelial RAGE that bound neutrophil-expressed Mac-1. 15 These findings implicate an important role of both endothelial and neutrophil expressed RAGE in Mac-1-dependent neutrophil recruitment during inflammation.Direct in vivo observations of leukocyte recruitment in the absence of RAGE have not been reported. To prove the hypothesis that RAGE is a relevant Mac-1 ligand under in vivo conditions and dissect the contribution of endothelial and neutrophil expressed RAGE in mediating leukocyte recruitment in respect to its role as Mac-1 ligand, we studied RAGE-dependent leukocyte adhesion by intravital microscopy in an acute trauma-induced model of inflammation.…”
mentioning
confidence: 88%
“…Earlier RAGE has been shown to be involved in cell recruitment; RAGEdeficient mice displayed a diminished number of adherent inflammatory cells on the peritoneum after cecal ligation and puncture (CLP) (24) and a reduction in neutrophil influx in the peritoneal cavity after thioglycolate peritonitis (36). In addition, in vitro studies have suggested that RAGE is an endothelial counterreceptor for the ␤ 2 integrin Mac-1 (35,36), and that a functional interplay between RAGE and Mac-1 on leukocytes is required for HMGB1-mediated inflammatory cell recruitment (34). Our findings that RAGE Ϫ/Ϫ mice have a diminished neutrophil recruitment to the lungs during S. pneumoniae are in line with these data.…”
Section: Discussionmentioning
confidence: 99%
“…The viability of the monocytes was determined by trypan blue staining. An inhibitory anti-RAGE Ab was used, as previously described (18).…”
Section: Cells and Absmentioning
confidence: 99%